Layanan UNILA Library Mobile: Inovasi Teknologi Digital di Perpustakaan Universitas Lampung - Rd. Erni Fitriani (Institut Agama Islam Negeri Salatiga, 2018)
The development of information and communication technology (ICT) is maked by variouspatterns of information acquisition with various types and media formats. The presenceof mobile communication devices, online media, online games, web technology, socialnetworking applications such as: facebook, WhatsApp, line and other social networkingthat makes users stay connected. This phenomenon becomes a challenge for informationmanagers (librarians) and information providers (Library) to make changes through theapplication of information technology both in the library management and library services.The Library of Lampung University has innovated digital technology in library servicesthrough Unila Library Mobile service. The purpose of this research is to: 1) describe UnilaLibrary Mobile service as digital technology innovation of The Library of Lampung University;2) explain the advantages and disadvantages of Unila Library Mobile service. Thisresearch uses qualitative descriptive method with data collection through observation andliterature study. Observations to visitors of the Library of Lampung University, especiallyvisitors of reference services in the collection search process and tracing information online.Library study through literature-literature related to the object of this research. The resultof this research is Unila Library Mobile service is the digital technology innovation of TheLibrary of Lampung University as an effort to improve the utilization of Library service. TheUnila Library Mobile service has the advantage of providing library services in a practical,easy and efficient manner in utilizing them, but has disadvantages as well: Unila LibraryMobile service can not be accessed if the server at the Lampung University is eror; powerlines off; if you want to access outside the Lampung University must have free wifi; and ifyou want to access with a smartphone must have a quota.